Sobre la narrativa modernista valenciana: Eduard López-Chavarri - Simbor, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: After examining López-Chavarri's narrative, the author reaches the conclusion that it cannot be considered modernist in a literary sense, but recognises its important role in the modernization of Valencian prose at the beginning of the century.